DISCOLORATION IN RAW AND PROCESSED POTATO (Solanum Tuberosum) THROUGH SLOW HEATING PROCESS - Rizal Andi Syabana; Dody Tri Kurniawan; Isdiantoni Isdiantoni; Alam Islamy (Journal of Food Technology and Agroindustry dipublikasikan oleh Universitas Wiraraja, 2022)
In today’s world, it is known that potato become important commodity as it well spread around the continents. Because of not only nutrition content but also potato vastly consumed because of its highly yield per acre. However, there are some factors that contribute to the quality loss of potato itself, one of them is discoloration in raw potato. This experiment aimed to determine discoloration on some sort of potatoes due to cooking process. The experiment was conducted in the laboratory for sensory and consumer study, University of Goettingen from 04th to 08th of March 2019. There were three varieties of potato used in this experiment, namely Amanda (mealy potato), Queen Anne (mainly waxy potato), and Belana (waxy potato). The result was all samples experienced color changing as the number on each index are changing. Belana variety showed the lowest value of L and experienced the highest gap on before-after L value, which means this variety was the darkest among the other samples. The gap also high as before treatment value was 76,03 and become darker after treatment (63,53). On the contrary, Amanda variety experienced a slight darkening since the gap between before and after treatment was only 2.97 (from 74,34 to 71,37)